Nonadherence to antihypertensive drugs: A systematic review and meta-analysis - Abegaz, Tadesse Melaku; Shehab, Abdulla; Gebreyohannes, Eyob Alemayehu; Bhagavathula, Akshaya Srikanth; Elnour, Asim Ahmed (Medicine (Baltimore), 2017)
Hypertension drives the global burden of cardiovascular disease and its prevalence is estimated to increase by 30% by the year 2025. Nonadherence to chronic medication regimens is common; approximately 43% to 65.5% of patients who fail to adhere to prescribed regimens are hypertensive patients. Nonadherence to medications is a potential contributing factor to the occurrence of concomitant diseases. This systematic review applied a meta-analytic procedure to investigate the medication nonadherence in adult hypertensive patients. Original research studies, conducted on adult hypertensive patients, using the 8-item Morisky medication adherence scale (MMAS-8) to assess the medication adherence between January 2009 and March 2016 were included. Comprehensive search strategies of 3 databases and MeSH keywords were used to locate eligible literature. Study characteristics, participant demographics, and medication adherence outcomes were recorded. Effect sizes for outcomes were calculated as standardized mean differences using random-effect model to estimate overall mean effects. A total of 28 studies from 15 countries were identified, in total comprising of 13,688 hypertensive patients, were reviewed. Of 25 studies included in the meta-analysis involving 12,603 subjects, a significant number (45.2%) of the hypertensive patients and one-third (31.2%) of the hypertensive patients with comorbidities were nonadherent to medications. However, a higher proportion (83.7%) of medication nonadherence was noticed in uncontrolled blood pressure (BP) patients. Although a higher percentage (54%) of nonadherence to antihypertensive medications was noticed in females (P < 0.001), the risk of nonadherence was 1.3 times higher in males, with a relative risk of 0.883. Overall, nearly two-thirds (62.5%) of the medication nonadherence was noticed in Africans and Asians (43.5%). Nonadherence to antihypertensive medications was noticed in 45% of the subjects studied and a higher proportion of uncontrolled BP (83.7%) was nonadherent to medication. Intervention models aiming to improve adherence should be emphasized.